2023
DOI: 10.1088/2053-1583/ad10b9
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic two-dimensional silicon-oxide from natural silicates

Preeti Lata Mahapatra,
Caique Campos de Oliveira,
Gelu Costin
et al.

Abstract: Silicon dioxide’s potential for having magnetic properties is fascinating, as combining its electronic capabilities with magnetic response seems promising for spintronics. In this work, the mechanisms that drive the change from diamagnetic behavior in pure silicates like SiO2 to paramagnetic behavior in transition metal-doped silicates like Rhodonite silicate (CaMn3Mn(Si5O15)) are explored. This naturally occurring Rhodonite (R)-silicate was thinned down while retaining its magnetic properties by liquid-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Sensitivity was about 0.2/ppm with major H 2 S gas adsorption at Mn sites of the material. Figure 7(f) again shows a study reported recently on the magnetic properties of 2D silicate (2D Rhodonite) compared to diamagnetic SiO 2 [95]. The study elaborately discusses, supported by DFT results, how the presence of transition metal atoms like Mn in the structure has a significant role in the transition from diamagnetic to paramagnetic character for pure SiO 2 and CaMn 3 MnSi 5 O 15 , respectively [95].…”
Section: D Pyroxene and Pyroxenoidsupporting
confidence: 66%
See 4 more Smart Citations
“…Sensitivity was about 0.2/ppm with major H 2 S gas adsorption at Mn sites of the material. Figure 7(f) again shows a study reported recently on the magnetic properties of 2D silicate (2D Rhodonite) compared to diamagnetic SiO 2 [95]. The study elaborately discusses, supported by DFT results, how the presence of transition metal atoms like Mn in the structure has a significant role in the transition from diamagnetic to paramagnetic character for pure SiO 2 and CaMn 3 MnSi 5 O 15 , respectively [95].…”
Section: D Pyroxene and Pyroxenoidsupporting
confidence: 66%
“…It is clear that 2D silicates present a wealth of opportunities for fundamental research as well as applications in science and cutting-edge technology. We hope the present work will stimulate [94,95] further investigations on this remarkable class of 2D materials.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations